Mechanical shear stress and leukocyte phenotype and function: Implications for ventricular assist device development and use. Issue 3 (March 2019) - Radley, Gemma; Ali, Sabrina; Pieper, Ina Laura; Thornton, Catherine A
Heart failure remains a disease of ever increasing prevalence in the modern world. Patients with end-stage heart failure are being referred increasingly for mechanical circulatory support. Mechanical circulatory support can assist patients who are ineligible for transplant and stabilise eligible patients prior to transplantation. It is also used during cardiopulmonary bypass surgery to maintain circulation while operating on the heart. While mechanical circulatory support can stabilise heart failure and improve quality of life, complications such as infection and thrombosis remain a common risk. Leukocytes can contribute to both of these complications. Contact with foreign surfaces and the introduction of artificial mechanical shear stress can lead to the activation of leukocytes, reduced functionality and the release of pro-inflammatory and pro-thrombogenic microparticles. Assessing the impact of mechanical trauma to leukocytes is largely overlooked in comparison to red blood cells and platelets. This review provides an overview of the available literature on the effects of mechanical circulatory support systems on leukocyte phenotype and function. One purpose of this review is to emphasise the importance of studying mechanical trauma to leukocytes to better understand the occurrence of adverse events during mechanical circulatory support.